The Market - Between the Actor's Own Interest and the Public Interest - Stoilova, Viara (Research Papers, 2018)
The article focuses on the relationship between the actor's own interest and the public interest in the functioning of the market. The methodological approach to analyzing this relationship is based on the metaphor of „invisible hand“. The aim of the article is to justify the diminishing cooperative role of the "invisible hand" for the realization of the public interest. On the basis of the theoretical-analytical approach, the concepts of "own interest" and "public interest" are defined and the distinction between "own interest" and "selfish interest" is justified.
Keywords: Public interest; Own interest; Selfish interest; Invisible hand; Market